(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
In ultrathin lead films, the super conductance at the exceedingly two dimensional limit is explored, leading films down to two nuclear layers where there is just one quantum well channel. Scanning tunneling spectroscopy reveals that the local order of super conducts remains stable before two atomic layers, where the temperature of transformation drops sharply to below the exact structure of the film. Our result demonstrates that Cooper can shape even if its binding is heavily affected by the substratum on the last twodimensional electron channel